Vaccination With Oral Polio Vaccine Reduces COVID-19 Incidence - Yagovkina, Nadezhda V.; Zheleznov, Lev M.; Subbotina, Ksenia A.; Tsaan, Andrey A.; Kozlovskaya, Liubov I.; Gordeychuk, Ilya V.; Korduban, Anastasia K.; Ivin, Yury Y.; Kovpak, Anastasia A.; Piniaeva, Anastasia N.; Shishova, Anna A.; Shustova, Elena Y.; et al. (Frontiers in Immunology, 2022)
Background Effective response to emerging pandemic threats is complicated by the need to develop specific vaccines and other medical products. The availability of broadly specific countermeasures that could be deployed early in the pandemic could significantly alter its course and save countless lives. Live attenuated vaccines (LAVs) were shown to induce non-specific protection against a broad spectrum of off-target pathogens by stimulating innate immune responses. The purpose of this study was to evaluate the effect of immunization with bivalent Oral Poliovirus Vaccine (bOPV) on the incidence of COVID-19 and other acute respiratory infections (ARIs). Methods and Findings A randomized parallel-group comparative study was conducted in Kirov Medical University. 1115 healthy volunteers aged 18 to 65 were randomized into two equal groups, one of which was immunized orally with a single dose of bOPV “BiVac Polio” and another with placebo. The study participants were monitored for three months for respiratory illnesses including COVID-19. The endpoint was the incidence of acute respiratory infections and laboratory confirmed COVID-19 in both groups during 3 months after immunization. The number of laboratory-confirmed cases of COVID-19 was significantly lower in the vaccinated group than in placebo (25 cases vs. 44, p=0.036). The difference between the overall number of clinically diagnosed respiratory illnesses in the two groups was not statistically significant. Conclusions Immunization with bOPV reduced the number of laboratory-confirmed COVID-19 cases, consistent with the original hypothesis that LAVs induce non-specific protection against off-target infections. The findings are in line with previous observations of the protective effects of OPV against seasonal influenza and other viral and bacterial pathogens. The absence of a statistically significant effect on the total number of ARIs may be due to the insufficient number of participants and heterogeneous etiology of ARIs. OPV could be used to complement specific coronavirus vaccines, especially in regions of the world where the vaccines are unavailable, and as a stopgap measure for urgent response to future emerging infections. Clinical trial registration number NCT05083039 at clinicaltrals.gov https://clinicaltrials.gov/ct2/show/NCT05083039?term=NCT05083039&draw=2&rank=1